EXPRESSION OF NATIONAL-CULTURAL COMPONENTS IN CLOTHING LEXICAL UNITS: A COGNITIVE AND LINGUOCULTURAL ANALYSIS (ENGLISH AND UZBEK) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This study investigates the expression of national-cultural components in clothing lexical units in English and Uzbek from a cognitive and linguocultural perspective. Clothing terminology is not only a system of naming material objects but also a repository of cultural meanings, social values, and historical experiences. The research integrates conceptual metaphor theory, frame semantics, and prototype theory to analyze how clothing vocabulary encodes cultural identity. The findings reveal that Uzbek clothing lexicon demonstrates a stronger connection with tradition, symbolism, and ethnographic heritage, whereas English clothing terminology reflects functional, institutional, and globalized perspectives. The study contributes to cross-cultural linguistics by demonstrating that lexical units serve as cognitive models of cultural knowledge.